Critical assessment of a cancer/oncology journal that suddenly ceased publication: Journal of the Balkan Union of Oncology - Teixeira da Silva Jaime A. (Forum of Clinical Oncology)
This article provides a brief historical overview of a now-shuttered open access cancer/oncology journal, Journal of the Balkan Union of Oncology (JBUON), whose metrics peaked with a 2020 Clarivate Analytics journal impact factor of 2.533. JBUON suddenly ceased publication in December 2021. The scrutiny of JBUON papers of this PubMed-indexed journal at the post-publication website PubPeer revealed a myriad of ethical infractions and the likely association with paper mills. In addition to troubling information about JBUON’s publishing operations, this paper emphasizes the opaque manipulation of the content of an unknown number of papers, a procedure that is considered unscholarly, dishonest, or even predatory. The fatal publishing errors and mismanagement of this journal that led to its demise serve as a useful learning curve for other cancer/oncology journals that may feel tempted to manipulate the scholarly record, either to “save face” or give the impression of an error-free publication record.